The effect of applying sanctions on the discipline of class v students at MI Muhammadiyah Kenteng Nogosari - Muthiah Fauzi; Laila Hidayatul Amin; Alfian Eko Rochmawan; Ruslan Agus (At Turots: Jurnal Pendidikan Islam, 2024)
This research aims to determine the effectiveness of implementing sanctions on student discipline at Madrasah Ibtidaiyah Muhammadiyah Kenteng Nogosari Boyolali for the 2022/2023 academic year. The type of research used is a quantitative approach with an ex post facto research design. The population in this study was class V MI Muhammadiyah Kenteng which consisted of two classes A and B. Sampling used a saturated sampling technique or saturationsampling, which is a sampling technique if all subjects or objects in the population are used as samples. The data collection method in this research uses mean, median, mode, standard deviation, Likert scale scoring, in the prerequisite test using the Kolmogorov-Smirnov normality test and homogeneity test using the Levene test and paired sample t-test using the SPSS version 15.0 application.  Based on the results of data analysis on the application of sanctions using the data centering formula of mean, median, mode, standard deviation and scoring, the results show a mean of 75.6, a median of 74.7, a mode of 74.7, a standard deviation of 120.4 and a very high Likert scale scoring with a total of 8 students, high with 19 students, low with 13 students and very low with 7 students. Meanwhile, the results of the analysis of student discipline data showed that the mean was 80, the median was 74.7, the mode was 74.7, the standard deviation was 12.001 and the Likert scale scoring was very high with the number of 11 students, high with 14 students, low with the number of 17 students, very low with the number 5 students. Based on the results of the prerequisite test calculations using the normality test with the Kolomogorof - Smirnov test formula, the researcher obtained a significant ASYMP sig value. (2-tailed) was 0.877, indicating that the residual value was normally distributed, and the homogeneity test which was tested using the researcher's Levene test formula obtained a significant value of 0.976, indicating that the data were homogeneous. Next, calculate the hypothesis test using the paired sample t-test formula. The results of the t table value show l t count l = 3.562 > t table = 2.013 so Ho is rejected. Meanwhile, the significant value shows sig. (2-tailed) is 0.001<0.05, then Ho is rejected. This means that there are differences after implementing sanctions and student discipline at MI Muhammadiyah Kenteng Nogosari.